Sunflower protein films incorporated with clove essential oil have potential application for the preservation of fish patties - Salgado, Pablo Rodrigo (2013)
The incorporation of sunflower protein films with clove essential oil and the application of the resulting materials on the preservation of sardine patties were studied. The addition of clove essential oil to formulations based on sunflower protein concentrates allowed to prepare biodegradable and edible films with increased antioxidant properties and important in vitro antimicrobial properties. The presence of clove essential oil modified protein interactions reducing water solubility and glass transition temperature of resulting films, but it did not modify markedly their moisture content, thickness, color, opacity, water vapor permeability and mechanical properties. When applied to the preservation of refrigerated sardine patties these films allowed to retard fish lipidic auto-oxidation and to slightly delay the growth of total mesophiles, proving once again the importance of checking the films functionality in real food systems.